Effect of polyvinylpyrrolidone concentration in the substrate of thin-film composite forward osmosis membrane on neodymium removal - Yeoh, Yuan Xin; Mazrul Nizam, Abu Seman; Mohd Yusri, Mohd Yunus; Mohammad, Abdul Wahab (Malaysian Institute of Chemistry, 2024)
Secondary rare earth element (REE) resources need to be explored due to the increased global demand for REEs across all industries. Without the practice of a circular economy that fully utilises secondary REE resources, primary REE resources will deplete in the future. Therefore, this study suggests the recycling of REE from acid mine drainage (AMD) caused by mine tailings in upstream and midstream processes. This study implemented forward osmosis (FO) using a thin-film composite (TFC) membrane to remove neodymium (Nd) from synthetic AMD. The pore-forming agent, polyvinylpyrrolidone (PVP), with various concentrations, was used in the production of polyethersulfone (PES) porous substrate to serve as a support for the TFC FO membrane. A thin-film active layer of polyamide was formed on the top surface of the PES membrane support through the interfacial polymerisation method using 2 wt% of aqueous mphenylenediamine and 0.15 wt% of trimesoyl chloride. The addition of PVP to the dope solution increased the substrate's porosity, making it more suitable for the FO process. The TFC FO PES membrane prepared from a substrate with 10 wt% PVP was proven to be the most effective in Nd removal, achieving 93.11% efficiency.